Pengaruh Edukasi Penggunaan APD Masker Terhadap Tingkat Pengetahuan Dan Resiko ISPA Pada Lansia Pengolah Kapuk Di Desa Dalaka Kecamatan Sindue - Rafiqa, Siti Nur; Adesulistyawati, Adesulistyawati; Rammang, Sisilia (Jurnal Ners, 2024)
ARTI is a disease transmitted by viruses. Most of these diseases are transmitted through droplets, but it does not have the possibility of transmission through other ways such as contact with contaminated hands or other objectsThe study's goal is to comprehend how education affects by using PPE masks on the knowledge level and risk of ARTI in elderly kapuk production in Dalaka Village, Sindue District. This Quasi-Experimental research design combined with quantitative research (pseudo-experimental research) using a pair of pre- and post-test controls group design. The total population was 162 people and the whole sample was 44 respondents taken by Nonprobability Sampling technique, with Accidental sampling type. The results showed that most of the intervention group about 22 respondents (100.0%) have a good level of knowledge. About 11 respondents (50%) as the percentage of ARTI risk (Posttest) each for the risk and non-risk categories. The Wilcoxon test analysis findings display a 0.000 <0.05 significant value. The outcome said that education has an impact on using the PPE masks on the knowledge level and risk of ARTI in elderly of kapuk production in Dalaka Village, Sindue District. Suggestions should conduct health counseling in the community, especially for the elderly kapok production regarding ARTI disease and the using of masks to reduce the incidence of ARTI.